CP-190 Impact of the deployment of a clinical pharmacy team in endocrinology–nutrition unit. (25th February 2017) - Breuker, C; Clement, F; Audurier, Y; Renaudin, P; Boegner, C; Jalabert, A; Villiet, M; Castet-Nicolas, A; Avignon, A; Sultan, A
Abstract : Background: Since 2003, the American Diabetes Association has included pharmacists in the list of diabetes care team members. Indeed, the intervention of clinical pharmacists (CP) has been associated with a decreased risk of medication error (ME) and therefore contributes to the safety of medication management during patients' healthcare circuit. Purpose: The aim of this study was to evaluate the impact of CP activities dispensed by pharmacists in an endocrinology–nutrition unit. Material and methods: An observational, prospective, monocentric study was conducted between November 2013 and September 2016 in a nutrition–endocrinology unit (50 beds). 1 senior, 1 junior and 3 student pharmacists were involved in the deployment of clinical pharmacy activities (medication reconciliation at admission and discharge with delivery of drug management plans (DMP), interview of patient (measurement of medication adherence using the Morisky scale (MMAS-4), assessment of drug knowledge (indication, dosage and precautions for use) and risk of hypoglycaemia). All patients who provided verbal consent were entered into a registry with data collected from their hospitalisation, including anthropometric, clinical, therapeutic and biological information (No DC-2009–1052). Results: 1655 and 1570 patients received medication reconciliation at admission and discharge, respectively. 596 ME in 407 patients were detected and corrected, most were drug omissions. 597 DMP were explained and delivered to patients. 255 patients received an interview with measurement of medication adherence and assessment of drug knowledge. 64 patients had a low level of adherence, the indication, dosage and precautions for use of medications were known, respectively, in 70%, 80% and 44% of cases. Of the 358 patients interviewed about the risk of hypoglycaemia, respectively, 83 (23%) and 127 (35%) patients reported having had at least one severe hypoglycaemia incident in the year and more than one hypoglycaemia incident by week. Conclusion: Deployment of a clinical pharmacy team in the nutrition–endocrinology unit was a complete success. The CP activities allowed safe drug management with the correction of a significant number of ME before they resulted in harm, and highlighted patients requiring therapeutic education. The next step will be to demonstrate that clinical activities dispensed by pharmacist can decrease rehospitalisation of patients with endocrine diseases. No conflict of interest